Elkraftseffektivisering av SSAB i Luleå - Ljunggren, Magda (2014)
The aim of this master thesis was to help formulate an electrical consumption plan for SSAB in Luleå. The consumption plan is based on a number of efficiency measures which was investigated for various help systems. The help systems affected in this work are engine pre-heaters, lightning, ventilation, pumps, fans, transformers and to some extent electric motors. An important delimitation for this work has been to study units that can act as leading examples for future efficiency work. The project resulted in a number of appropriate efficiency measures with great savings potential and a short payback period. For some help systems a full study has been performed while it for others only has been possible to estimate the potential savings. Engine pre-heaters are always running when the temperature is below 10°C. In this study the possibility of introducing controlling have been examined. This would reduce the operating costs by about 80 percent with a payback period of just over two years. The total operating costs can be reduced by nearly 1 million SEK per year with the proposed action. The current choice of lightning and controlling differ greatly between locals and subareas. In office buildings with older lightning systems a change of light source demonstrated the largest effect. With this measure, the energy costs are reduced with 50 - 60 percent depending on the current situation and the choice of light source. The substations reached the largest energy savings through the introduction of presence control. This measure results in large savings with a very low investment cost. The saving potential is strongly dependent on current lightning control and use and can at best reduce the costs by 83 percent. Workshops use a large amount of mercury- and metal halogen lamps. These lamps have a high installed effect and a long ignition time which means that they are rarely switched off. Because of this both the use of more effective light sources and the introduction of presence control lead to large savings. Together, ...